Superconductivity at 253 K in lanthanum–yttrium ternary hydrides. (September 2021) - Semenok, Dmitrii V.; Troyan, Ivan A.; Ivanova, Anna G.; Kvashnin, Alexander G.; Kruglov, Ivan A.; Hanfland, Michael; Sadakov, Andrey V.; Sobolevskiy, Oleg A.; Pervakov, Kirill S.; Lyubutin, Igor S.; Glazyrin, Konstantin V.; Giordano, Nico; et al.
Graphical abstract: Abstract: Here we report the high-pressure synthesis of a series of lanthanum–yttrium ternary hydrides obtained at pressures of 170–196 GPa via the laser heating of P 63 /mmc La–Y alloys with ammonia borane. As a result, we discovered several novel compounds: cubic hexahydride (La, Y)H6 and decahydrides (La, Y)H10 with a maximum critical temperature T C ∼ 253 K and an extrapolated upper critical magnetic field B C2 (0) of up to 135 T at 183 GPa. The current–voltage measurements show that the critical current density J C in (La, Y)H10 is 12–27.7 kA/mm 2 at 4.2 K, which is comparable with that of commercial superconducting wires such as NbTi and Nb3 Sn. (La, Y)H6 and (La, Y)H10 are among the first examples of ternary high- T C superconducting hydrides. Our experiments show that part of metal atoms in the structures of recently discovered Im 3 ¯ m -YH6 and Fm 3 ¯ m -LaH10 can be replaced with lanthanum (∼70%) and yttrium (∼25%), respectively, with the formation of unique ternary superhydrides containing metal-encapsulated cages La@H24 and Y@H32, which are specific for Im 3 ¯ m -LaH6 and Fm 3 ¯ m -YH10 . This work demonstrates that hydrides, unstable in pure form such as LaH6 and YH10, may nevertheless be stabilized at relatively low pressures in solid solutions with superhydrides having the desired structure.